In search of space - J-A. van den Berg (Acta Theologica)
From text: In professional jargon, architects often refer to the entrance of a particular building. This is a direct allusion to, inter alia, the design and the way in which it influences the aesthetic sense-impressions with which a specific space is entered. In the corresponding space which will be entered in this study, the search for a relevant theologia habitus that has meaning for the future workplace will be mapped out. This quest for an appropriate presentation of a relevant theologia habitus for the future workplace will be informed from the vantage point(s) of an interdisciplinary dialogue between practical theology and futures studies, as formulated and guided on the basis of narrative (auto)biographical accents.